Análisis electronergético argentino - Csik, B. J.; Sarraillet, Hugo; Marrero, Héctor M. (Comisión Nacional de Energía Atómica (Argentina), 1973)
Fil: Csik, B. J. Comisión Nacional de Energía Atómica; Argentina